2012
DOI: 10.1017/s146114571100201x
|View full text |Cite
|
Sign up to set email alerts
|

A systematic review of the evidence of clozapine's anti-aggressive effects

Abstract: Reducing the risk of violent and aggressive behaviour in patients with schizophrenia remains a clinical priority. There is emerging evidence to suggest that the second-generation antipsychotic, clozapine, is effective at reducing this risk in patients with schizophrenia and some evidence to suggest that it may be best in selected patients. We conducted a systematic literature search in March 2011 of all prospective and retrospective studies, which investigated clozapine's anti-aggressive effects in a variety o… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

5
108
0
13

Year Published

2014
2014
2024
2024

Publication Types

Select...
5
2
1

Relationship

0
8

Authors

Journals

citations
Cited by 194 publications
(130 citation statements)
references
References 131 publications
5
108
0
13
Order By: Relevance
“…It has also been suggested that earlier use (as a second line agent) can be recommended in individuals with persistent hostility/aggressive behaviour [47] and suicidalilty [39][40][41][42]. In fact the indication for recurrent suicidal behavior has been officially approved by the FDA [48].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…It has also been suggested that earlier use (as a second line agent) can be recommended in individuals with persistent hostility/aggressive behaviour [47] and suicidalilty [39][40][41][42]. In fact the indication for recurrent suicidal behavior has been officially approved by the FDA [48].…”
Section: Discussionmentioning
confidence: 99%
“…Reasons for physicians' reluctance to prescribe clozapine have been evaluated and the relatively high incidence of agranulocytosis has certainly had great influence; however, the careful monitoring of WBC counts and ANC has almost completely abolished the risk of fatal agranulocytosis; frequency of blood tests has recently been simplified and once WBC counts and ANCs have been maintained within normal levels for one year, blood tests are now only required once every 4 weeks [27,47]. It is also of importance to note that in some European countries a more flexible monitoring schedule, which can be reduced to quarterly blood testing in individuals not at risk, has been proposed [59,60].…”
Section: Discussionmentioning
confidence: 99%
“…However, the major drawback of atypical antipsychotics are side effects such as weight gain, metabolic changes, sleep disturbances, higher risk of sedation and tremor, drooling, increased appetite, fatigue, dizziness, and withdrawal dyskinesias [29,30]. Another atypical antipsychotic drug, clozapine, has been shown to be effective against hyperactivity and aggression in children with ASD [31].Therefore, based on limited evidence with small sample sizes and short follow-ups, atypical antipsychotics may be more effective as short-term interventions for certain behavioral symptoms in patients with ASD.…”
Section: Antipsychoticsmentioning
confidence: 99%
“…Dolayısıyla şizofreni hastalarında şiddete giden yol çokludur ve bu sebepsel karmaşıklık tedavide de önem sergilemektedir. [47] Şiddet Olgusuna Akut Yaklaşım www.cappsy.org Öncelikle güvenlik sağlanmalı, tehlikeli olabilecek eşyalar uzaklaştırılmalıdır. Hastaya karşı saygılı, empatik ve ilgili bir tutumla görüşme yapılmalıdır.…”
Section: Klinik öZelliklerunclassified
“…[13,55] Olanzapinin; haloperidol, ketiyapin ve amisulpirid ajanlarının şiddet azaltıcı etkinliğine olan üstünlüğü bildirilmiş-tir. [47] Yapılan çalışmalarda, risperidonun şiddet davranışını azaltıcı etkisi bildirilmiş-tir. [56,57] Randomize çift-kör uygulanmış bir çalışmada şizofreni tanılı hastalarda şiddet davranışını azaltmakta plaseboya üstünlüğü gösterilmiştir.…”
Section: Farmakolojik Tedaviunclassified